Vedolizumab is effective and safe in elderly inflammatory bowel disease patients: a binational, multicenter, retrospective cohort study. Issue 9 (1st November 2020) - Cohen, Nathaniel Aviv; Plevris, Nikolas; Kopylov, Uri; Grinman, Anna; Ungar, Bella; Yanai, Henit; Leibovitzh, Haim; Isakov, Naomi Fliss; Hirsch, Ayal; Ritter, Einat; Ron, Yulia; Shitrit, Ariella Bar‐Gil; et al.
Abstract : Background: Immune modulating therapies are associated with an increased risk of infections and malignancies. This is of particular concern in elderly inflammatory bowel disease patients. This study aims to compare the safety and efficacy of vedolizumab between young and elderly inflammatory bowel disease patients. Methods: A binational, multicentre, retrospective, cohort study was performed from 2015 to 2019. Patients who underwent treatment with vedolizumab and were followed for at least 14 weeks were studied. They were divided according to age into groups: 40 years or less or 60 years or older. Clinical and endoscopic responses at weeks 14 and 52 and infection development were compared between young and elderly inflammatory bowel disease patient groups. Results: There were 144 patients (82 Crohn's disease and 62 ulcerative colitis) in the elderly cohort and 140 patients (83 Crohn's disease and 57 ulcerative colitis) in the young cohort. The average age was 70.2 ± 7.3 years and 29.6 ± 5.7 years, respectively. Clinical and endoscopic responses were comparable between the groups (week 52 remission of Crohn's disease: 40% vs. 35%, P  = 0.7; week 52 remission of ulcerative colitis: 48% vs. 51%, P  = 0.84). Previous anti‐tumour necrosis factor biological therapy was independently associated with poor clinical remission rates at week 52 (Crohn's disease: odds ratio 0.23, 95% confidence interval 0.06–0.79; P  = 0.02 and ulcerative colitis: odds ratio 0.10 95% confidence interval 0.01–0.74; P  = 0.024). There were significantly more infections in the elderly cohort (2% vs. 12%, P  = 0.002), none of which were fatal. Conclusions: Vedolizumab is equally effective in elderly and young inflammatory bowel disease patients. The findings of this study demonstrate an increased risk of infections among the elderly treated with vedolizumab, which may be related to their age and underlying diseases.